PANDANGAN SIYASAH DUSTURIYYAH TERHADAP TUPOKSI BADAN PERMUSYAWARATAN RAKYAT NAGARI DALAM MENYUSUN PERATURAN NAGARI - Roma Ramadhani; Dian Pertiwi (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2022)
The main problems in this thesis are, How is the main function of the Nagari People's Consultative Body implemented in drafting Nagari regulations, and how is Siyasah Dusturiyyah's view of the implementation of the main duties and functions of the Nagari People's Consultative Body in drafting Nagari regulations. The purpose of this thesis is to find out and explain the implementation of the main functions of the Nagari People's Consultative Body in drafting Nagari regulations, and to find out and explain Siyasah Dusturiyyah's views on the main tasks and functions of the Nagari People's Consultative Body in drafting Nagari regulations